On the influence of Mn on the phase stability of the CrMnxFeCoNi high entropy alloys. (January 2018) - Christofidou, K.A.; Pickering, E.J.; Orsatti, P.; Mignanelli, P.M.; Slater, T.J.A.; Stone, H.J.; Jones, N.G.
Abstract: The fcc phase of the equiatomic high entropy alloy, CrMnFeCoNi, has been recently shown to be unstable at temperatures below 800 °C. However, the stability of the constituent CrFeCoNi quaternary alloy, which forms the basis of many other high entropy systems, remains under debate and the existing literature contains very little long duration heat treatment data. Here, the phase equilibria of CrFeCoNi and CrMn0.5 FeCoNi are assessed following 1000 h exposures at 500, 700 and 900 °C. Prior to thermal exposure the cast alloys were homogenised and shown to exist as single phase fcc solid solutions. In line with previous reports, Cr rich particles were observed on the grain boundaries following the prolonged exposures but detailed electron microscopy showed that these features were M23 C6 carbides resulting from the unintentional incorporation of C during production. However, no evidence was found for any other phase formation during the heat treatments of either alloy, in direct contrast to the results for CrMnFeCoNi. Consequently, it is concluded that, within the limits of the temperature and times considered, the solid solution phases of both CrFeCoNi and CrMn0.5 FeCoNi are stable and that Mn has a destabilising influence when present in sufficient concentrations. This change in behaviour occurs for a Mn content between 11.1 and 20 at.%. Graphical abstract: Highlights: Three CrMnx FeCoNi alloys studied following 1000 h at 500, 700 and 900 °C. Cr rich grain boundary phase in CrFeCoNi and CrMn0.5 FeCoNi shown to be M23 C6 . No intermetallic phases found in CrFeCoNi or CrMn0.5 FeCoNi, unlike CrMnFeCoNi. CrFeCoNi and CrMn0.5 FeCoNi are stable as single phase solid solutions. Critical Mn content that destablises solid solution phase between 11 and 20 at.%.